Ruthenium Complexes Bearing Thiophene‐Based Unsymmetrical N‐Heterocyclic Carbene Ligands as Selective Catalysts for Olefin Metathesis in Toluene and Environmentally Friendly 2‐Methyltetrahydrofuran. Issue 57 (19th September 2018) - Smoleń, Michał; Kośnik, Wioletta; Gajda, Roman; Woźniak, Krzysztof; Skoczeń, Aleksandra; Kajetanowicz, Anna; Grela, Karol
Abstract: Three mono‐ N ‐heterocyclic carbene (NHC) ruthenium 2‐isopropoxybenzylidene (10 a –c ) and one bis(NHC) indenylidene complex (8 ) bearing an unsymmetrical N ‐heterocyclic carbene ligand were synthesized and structurally characterized by single‐crystal X‐ray diffraction. The catalytic activity of the newly obtained complexes were evaluated in ring‐closing metathesis (RCM) and ene–yne (RCEYM) reactions in toluene and environmentally friendly 2‐MeTHF under air. The results confirmed that although all tested reactions can be successfully mediated by catalysts 10 a –c, their general reactivity is lower than the benchmark all‐purpose Ru catalysts with symmetrical NHC ligands. However, the latter cannot compete with specialized ruthenium complex 10 a in industrially relevant self‐CM of terminal olefins in neat conditions. Abstract : Joining the elite : New "special tasks" catalysts have been developed. They exhibited much better reactivity than the commercially available complexes in self‐metathesis reactions of α‐olefins, enabling high yields and selectivities to be reached.